Application of coherent light in measuring optical property and blood perfusion - Bi, Renzhe (2015)
Coherent light source is widely utilized in biomedical study. In this thesis, the coherent light is mainly applied for measuring the optical property and in vivo blood perfusion. An interesting physiological phenomenon, coherent backscattering (CBS) is introduced. People have found many biomedical applications of CBS related technologies. Through our study, the illumination beam size on the sample is shown to affect the CBS phenomenon significantly when its diameter is small. The coherent light source is highly auto-correlated in time domain. The electric field temporal autocorrelation function of the light will decay faster when the photons are collided with moving particles, such as the in vivo red blood cells. This is the foundation of many optical modalities for blood perfusion measurement, such as diffuse correlation spectroscopy (DCS). A software correlator based DCS system is introduced in this thesis. We validate its performance by a flow-controlled phantom. Interesting in vivo data is also demonstrated. To simplify DCS system, a novel optical modality for deep tissue blood perfusion measurement, diffuse speckle contrast analysis (DSCA) is introduced for the first time by the author. DSCA brings several advantages in instrumentation and data processing, which may find significant clinical applications. Relative validation results against our home made DCS system are demonstrated. There are already several existing optical modalities for blood perfusion measurement in the market, such as laser Doppler Flowmetry and laser speckle contrast imaging. In this thesis, the working principles of these existing optical blood perfusion monitoring technologies are studied and compared in details. The relationship and comparison among these optical technologies are discussed in details. In summary, this dissertation introduces some biomedical applications of the coherent light, especially in optical property measurement and blood perfusion mornitoring.